From Ontology Design to User Experience. A Methodology to Design Interfaces for Information Seeking Purposes - Marco Grasso; Marilena Daquino; Giulia Renda (Umanistica Digitale)
When designing data-driven web applications, users’ informative needs are aligned to knowledge organization (KO) requirements, which are secondly mapped to user interfaces (UI) components, and finally to user experience (UX) journeys. Particularly, when data are served as Linked Open Data, data and user requirements can be associated with competency questions that an ontology should address. However, to the best of our knowledge, there is no full-fledged methodology that systematically adopts ontology requirements to design UI components and UX journeys. In this article we propose a methodology to design web applications for information seeking purposes that leverages well-known ontology design methodologies and UI/UX approaches. We present a case study based on music heritage and we evaluate it via a user study.